Model Pencarian Informasi Pada Generasi Milenial Mahasiswa IPI Pascasarjana UIN Sunan Kalijaga Yogyakarta Angkatan 2018 - Sander, Ali; Masruri, Anis (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
ABSTRACT Introduction. nformation is a medium that has high use value. For everyone, the need for information is everything for the sake of carrying out daily activities. The purpose of this study in general is to find out the information seeking model for IPI Postgraduate students of UIN Sunan Kalijaga Yogyakarta class of 2018, these students are included in the millennial generation. Specific or more specific objectives in this research are; (a) to determine the variety of generations, (b) to find out the information needs of students, (c) to find out the origins of information seeking sources, (d) to find out information seeking models, (e) and to find out barriers to information seeking Data Collection Method. This research is a descriptive qualitative research, using a case study model. The determination of the research subjects was carried out by using purposive sampling technique. This research uses information theory. The informants in this study were 13 students of postgraduate IPI concentration class 2018. The data collection techniques in this study used interview techniques and documentation study. Results and Discussions. Based on the results of interviews and data analysis conducted, the results indicate the need for information on IPI postgraduate class 2018 students in the form of; books, internet journals, videos, recordings, and literature related to IPI concentration. Sources of information used by students are; books, reading rooms in libraries, internet, seminars, and human resources. Information seeking model by students in the form of; Ellis' model: starting, chaining, browsing, differentianting, mentoring, extracting. Conclusions. Using methods or models to obtain information, and obstacles in obtaining information cannot be avoided because of the limited skills students have. The Ellis model is a model or search for the right information to be implemented by IPI postgraduate students of class 2018